Cultural studies in question - Ferguson, Marjorie; Golding, Peter (Sage Publications, 1997)
This major text offers a critical reappraisal of the contemporary practice of cultural studies. It focuses in particular on the contribution of cultural studies to the understanding of media, communications and popular cultures in contemporary societies. The contributors, an outstanding group of internationally acclaimed scholars, examine topics such as: the different strands of cultural studies and how they are developed; whether cultural studies is a coherent discipline; tensions and debates within cultural studies; alternative or related approaches to contemporary media and society; and the movement by cultural studies revisionists towards more empirical and sociological modes of analysis.